Quantification of Pregenomic RNA and Covalently Closed Circular DNA in Hepatitis B Virus-Related Hepatocellular Carcinoma - Fugui Bai; Yoshihiko Yano; Takumi Fukumoto; Atsushi Takebe; Motofumi Tanaka; Kaori Kuramitsu; Nungki Anggorowati; Hanggoro Tri Rinonce; Dewiyani Indah Widasari; Masaya Saito; Hirotaka Hirano; Takanobu Hayakumo; et al. (International Journal of Hepatology)
Pregenomic RNA (pgRNA) is generated from covalently closed circular DNA (cccDNA) and plays important roles in viral genome amplification and replication. Hepatic pgRNA and cccDNA expression levels indicate viral persistence and replication activity. This study was aimed to measure hepatic pgRNA and cccDNA expression levels in various states of hepatitis B virus (HBV) infection. Thirty-eight hepatocellular carcinoma (HCC) patients, including 14 positive for hepatitis B surface antigen (HBsAg) and 24 negative for HBsAg but positive for anti-hepatitis B core (anti-HBc) antibody, were enrolled in this study. In HBsAg-negative but anti-HBc-positive group, HBV-DNA was detected in 20 of 24 (83%) noncancerous liver tissues for at least two genomic regions based on polymerase chain reaction (PCR) analysis. pgRNA and cccDNA expression levels in occult HBV-infected patients were significantly lower than those in HBsAg-positive patients (P<0.001). pgRNA and cccDNA in cancerous tissues were also detected without significant difference from those in noncancerous tissues. In conclusion, cccDNA and pgRNA are detected and represented HBV replication not only in noncancerous but also in cancerous liver tissues. In addition, the replication is shown in not only patients with HBsAg-positive but also occult HBV-infected patients, suggesting the contribution to HCC development.